Managerial vote ownership and shareholder wealth - Chang, Saeyoung; Mayers, David (Journal of Financial Economics, 1992)
We examine employee stock ownership plan (ESOP) announcements to study the effects of an increase in managerial voting rights without a proportional increase in the ownership of cash flow claims. Our finding that when managers initially control few votes firm value increases with the fraction of shares contributed to the ESOP supports the view that managerial vote control serves shareholder interests. Conversely, the decrease in firm value with larger contributions to the ESOP when managers initially control many votes reflects a divergence of incentives that increases the agency problems between managers and outside shareholders.